The Structural Model of Predicting Marital Intimacy Based on Forgiveness and Cognitive Flexibility with the Mediating Role of Marital Boundaries - Mohammadpoor, Mahya; Houshyari, Jafar (Mental Health and Lifestyle Journal, 2024)
The aim of the present study was to determine the structural model for predicting marital intimacy based on forgiveness and cognitive flexibility, with the mediating role of marital boundaries. The research method was descriptive and correlational in nature. The statistical population consisted of all married individuals residing in the city of Qom in 2023. From this population, 257 individuals were selected using a non-random, convenience sampling method. The data collection instruments included the Bagarozzi Marital Intimacy Questionnaire (2001), the Ehteshami Forgiveness Scale (2009), the Dennis and Vander Wal Cognitive Flexibility Inventory (2010), and the Houshyari et al.'s Marital Boundaries Questionnaire (2020). For data analysis, structural equation modeling (SEM) was used with the SPSS-26 and PLS software. The results indicated that marital boundaries play a mediating role in the relationship between forgiveness and marital intimacy, fully mediating this relationship. Furthermore, marital boundaries partially mediated the relationship between cognitive flexibility and marital intimacy. Therefore, the presence of marital boundaries allows couples to establish personal limits, remain committed to their marital life, and subsequently improve their marital relationship and intimacy.